Fallin' up : my story - Taboo, 1975- (Simon & Schuster, 2011)
Taboo, Grammy Award-winning founding member of the Black Eyed Peas, shares the inspiring story of his rise from the mean streets of East L.A. to the heights of international fame.--From publisher description.